"Evaluate What I Was Taught, Not What You Expected Me to Know": Evaluating Students' Arguments Based on Science Teachers' Adaptations to Toulmin's Argument Pattern. Issue 3 (3rd April 2021) - Lazarou, Demetris; Erduran, Sibel
ABSTRACT: The paper examines how science teachers' instructional adaptations to Toulmin's Argumentation Pattern (TAP), made during the first time the framework is introduced to students as a learning heuristic for structuring their arguments, could contribute to the way the quality of students' arguments is evaluated. We first depict these adaptations, that mainly refer to the way each component of TAP was defined to students; the sequence one may choose to follow in order to express these components; and the specific argumentative indicators that may be used. We then analyze a number of students' written arguments in two ways. First we use Toulmin's own definitions of the components, with the help of argumentative indicators, which is an analytical method often utilized in research studies in science education. Second, we compare and contrast this analysis with a supplementary analysis that mainly uses, as coding categories, the teachers' adapted definitions of the TAP's components. The findings of the study suggest that, an awareness of the adaptations that science teachers make to TAP during the first time it is introduced to students seems to improve the trustworthiness of the analysis of students' work and of their learning outcomes.